LAJU RESAPAN ALIRAN PERMUKAAN OLEH LUBANG RESAPAN GEOPORI PADA LAHAN PERTANIAN PASCA PANEN - Rarun, Suharti; Kalangi, J. I.; Saroinsong, F. B. (Universitas Sam Ratulangi, 2019)
In the last few years, many forests in Indonesia have experienced changes in land use to agricultural land, this has implications for the emergence of environmental problems, namely an increase in surface flow that causes flooding . Geopore technology or geopore infiltration hole is a technology that can be used to reduced rainwater runoff by absorbing more volume of rainwater into the soil and can help to maintain the presence or availability of ground water. This study aims to determine the percentage of surface flow reduction by geopore infiltration holes in land-based trees, reeds and open land. This study aims to determine the volume of surface flow and the rate of infiltration of rainwater on post-harvest agricultural land. The method in this study used a was randomized block design as a data collection method which was then analyzed using descriptive analysis. The results of this study showed that the average rainfall intensity of 16.36 mm / hour obtained an average rate of recharge on post-harvest agricultural land without geopore which was 65 mm / hour and the average rate of recharge on agricultural land with geopore infiltration holes namely 148 mm / hour.